A Vehicle Collision Detection Algorithm at T-Shaped Intersections Based on Location-Based Service - Wang, Pin; Zhang, Lanfang; Fang, Shou’en; Wang, Junhua (New Frontiers in Road and Airport Engineering)
Collisions at intersections are considered a main contributor to the relatively high accident rates in China. One of the reasons is that drivers cannot get the full information needed to make an objective judgment about road conditions ahead. If collision detection is made and issued before drivers notice the danger, it would be of great importance for improving the traffic safety. In this paper, we proposed a collision detection algorithm to determine the possibility of collisions at T-shaped intersections based on location based service (LBS), which integrates global positioning system (GPS), inertial measurement unit (IMU), and other vehicle sensors to provide real-time state information of the vehicles approaching to the intersection. Results showed that the successful warning rate is as high as 81.7%, which indicates that the detection method is effective for alerting drivers to dangers beforehand.